Maintenance Logistics Management: A Survey Study in the Moroccan Industrial Context - Hammadi, Salima; Herrou, Brahim (International Journal of Supply Chain Management, 2020)
Global logistics system performance could not be achieved without an available intern logistics system for production systems.  Indeed, availability is the fastest path to performance where maintenance logistics occupies the central role.In this paper we define a systemic framework for maintenance logistics to manage all maintenance resources and their interactions.  In order to define main maintenance logistics management problems we conducted a structured survey study in the Moroccan industrial context. The study presents results based on 152 surveys responses from 281 surveys addressed to different industrial production systems. Results analysed on SPSS statistical software revealed an insufficient involvement level for production operator and insufficient organisation level for maintenance logistics environment. Therefore we propose a new sustainable model conception based on empirical conclusions. Keywords— Maintenance logistics system; management model; Operator involvement; maintenance logistics environment; SPSS software; maintenance improvement.